Class III β-Tubulin Overexpression Induces Chemoresistance to Eribulin in a Leiomyosarcoma Cell Line - Yahiro, Kenichiro (Anal Cell Pathol (Amst), 2018)
Eribulin is a new drug to treat soft tissue sarcoma (STS) that exerts antitumor activity by binding to microtubules. The prognosis of STS is poor, and eribulin is expected to improve the treatment outcome. We observed several cases that exhibited resistance to eribulin and developed an eribulin-resistant leiomyosarcoma cell line to investigate the mechanism of resistance. The IC50 of eribulin was 125 times higher in the resistant cell line than in the parental cell line, and eribulin did not induce G2/M arrest in resistant cells. The resistant cell line showed increased expression of MDR1 transcript, but protein levels and functional analysis results were similar to the parental cell line. We found that class III β-tubulin (TUBB3) was overexpressed in the resistant cell line, and siRNA knockdown of TUBB3 partially recovered sensitivity to eribulin. TUBB3 expression in clinical samples varied, suggesting that TUBB3 has the potential to be a biomarker for selection of anticancer drugs and may be a target for overcoming resistance to eribulin.